Relationship between personality traits and individual response to conflict situations in adolescents - Sandu, Mihaela Luminita; Rus, Mihaela; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2020)
The evaluation and treatment of internalizing disorders in children and adolescents has a long and rich tradition in the psychology and clinical psychiatry of the child. However, the use of longitudinal data to elucidate the evolution and outcome of these conditions, as well as their assessment and treatment, is less developed in the embryonic development stage. However, there have been interesting developments and significant progress has been made. The emergence of the field of developmental psychopathology in the last 10 years (Achenbach, 1982, Cicchetti, 1984; Rutter & Garmezy, 1983; Sroufe & Rutter, 1984), with emphasis on the continuity and discontinuity of the behavior between the embryonic phase, childhood, adolescence, is particularly welcome and timely, providing a good concern for the future. The identification of the dimensions of the personality structure is very important during the adolescence period, because during this period the correct development of the adolescents is based on stimulating several areas in close connection with their activity. A balanced teenager chooses activities that contribute to character development, self-confidence, socializing skills, identifying passions and making decisions. Behavior disorder can be defined as persistent disruptive behavior, in which the young person repeatedly violates the rights of others or the social norms corresponding to the age. It is often preceded by opposition and defiance in the early years and may become more skewed during adolescence. Symptoms include property damage, lying or theft, harassment, breaking rules and aggression against humans or animals. Adolescents with behavioral disorders often have concomitant disorders, such as depression, suicidal behavior, and poor relationships with peers and adults. Consequences include school problems, school expulsions, academic and professional failure and problems with the law. Parents and families need support to help ensure that young people do not get away from school, and that severely affected adolescents should turn to mental health professionals for assessment and care.